Assessing the Impact of Service Quality on Student Satisfaction: A Case Study of Barokatul Ishlah Islamic Boarding School Cooperative - Wahyuni, Fitri; Daud; Edi Saputra, Ahmad (Journal of Economics and Social Sciences (JESS), 2025)
Education serves as the fundamental cornerstone of national development, aiming not only to produce intellectually capable individuals, but also morally grounded, socially responsible, and skillful citizens. In Indonesia, pesantren (Islamic boarding schools) hold a strategic position within the educational system due to their holistic approach, which integrates religious instruction, character formation, and, increasingly, vocational training. This study aims to analyze the influence of service quality on student (santri) satisfaction at the cooperative of Barokatul Islah Islamic Boarding School, located in Rantau Karya Village, Tanjung Jabung Timur Regency. Employing a quantitative approach with an explanatory research design, the study adopts the SERVQUAL model, encompassing the dimensions of reliability, assurance, empathy, and responsiveness. A total of 101 student respondents were selected through purposive sampling. The results of a simple linear regression analysis indicate that service quality has a significant and positive effect on student satisfaction, with an R² value of 0.608 and a significance level of 0.000. These findings suggest that improvements in service quality—particularly in the dimensions of tangibles and empathy have a direct impact on student satisfaction. This research highlights the importance of managing pesantren cooperatives professionally and in alignment with Islamic values, in order to support the value-oriented, spiritual, and economically self-reliant educational goals of the pesantren system